Struktur Komunitas Makrozoobenthos di Perairan Muara Aek Tolang Pandan Provinsi Sumatera Utara - Zulkifli '; Cristianto ' (Ilmu Perairan (Aquatic Science), 2010)
The research conducted from at 14 to 21 May 2009 in Estuary of AekTolang Pandan, North Sumatera Province with aimed to find out macrozoobenthos community structure which includes species, abundance, diversity, dominance anduniformity, to know the relationship of the content of organic matter abundancemacrozoobenthos. The method used was survey method. Primary data obtained fromthe measurements and sampling at locations in the research and analysis in thelaboratory.Macrozoobenthos encountered in the study area there ware 17 generas of 3classes, namely class Gastropoda, bivalva and polychaeta. Individuals from the classof individuals who gastopoda was most often found. The average valuemacrozoobenthos abundance ranged from 33.77 to 197.33 ind/m2, the average valueof diversity index ranges between 1.20-2.17; dominance index value ranges between0.29-0.48; index value uniformity between 0.82-0.94 and the index of similaritybetween 0.23-0.4. Sediment organic matter content of the abundancemakrozoobenthos showed that correlation were middle and higher and positive, itmean higher in organic matter would lead to higher in macrozoobenthos.1)Lecture of Fishery and Marine Faculty2)Student of Fishery and Marine FacultyKeywords: Community, Macrozoobenthos, Estuary of Aek Tolang Pandan